Scientific Advances in STEM Synergies to Achieve Success. 2nd Edition - Torres Hernández, Yadir; Beltrán Custodio, Ana María; Félix Ángel, Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Following a previous topic (Scientific advances in STEM: from professors to students; https://www.mdpi.com/topics/advances_stem), this new topic aims to highlight the importance of establishing collaborations among research groups from different disciplines, combining the scientific knowledge from basic to applied research as well as taking advantage of different research facilities. Fundamental science helps us to understand phenomenological basics, while applied science focuses on products and technology developments, highlighting the need to perform a transference of knowledge to society and the industrial sector.